Changes in The Marsialapari Tradition in the Mandailing Batak Community in West Pasaman Regency - Yuslina; Gani, Maulid Hariri (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study discusses "Marsialapari  Tradition in the Mandailing Batak Community in Jorong Tanjung Durian, Nagari Seberang Kenaik , Gunung Tuleh District, West Pasaman Regency". The purpose of this study is to find out how the form of change in the implementation  of the Marsialapari tradition in the past with the present and the factors that cause changes in the Marsialapari  tradition in the Mandailing Batak Community in Jorong Tanjung Durian. The theory used in this study is the Social Change theory from Kingsley Davis. The method used in this study is a qualitative research method with an ethnographic method approach. The data collection techniques in this study are using observation, interviews, and documentation. The implementation  of the Marsialapari  tradition in the past and now, first,  the Marsialapari preparation process used to include determining the place of implementation, determining the time of implementation, mamio dongan, preparing tools and materials, stirring, preparing food. The two processes of the implementation  of Marsialapari used to include departing, starting work, mangankon dot manginim coffee, mangan kotu Dzuhur, mulak and in the implementation  of Marsialapari which now has some differences with the previous ones such as the determination of the system used, mamio dongan, departing, as well as when returning. The second finding is the factor that causes changes in the Marsialapari  tradition in the Mandailing Batak Community in Jorong Tanjung Durian, the factor that causes the change due to modernization, urbanization, economic improvement, social change, and the lack of interest of the younger generation in the Marsialapari tradition.